Application of composite conducting polymers for improving the corrosion behavior of various substrates: A Review - Bazli, Leila; Yusuf, Mohammad; Farahani, Ali; Kiamarzi, Morvarid; Seyedhosseini, Zahra; Nezhadmansari, Mehran; Aliasghari, Maryam; Iranpoor, Marjan (Journal of Composites and Compounds, 2020)
One of the most important problems in the manufacturing industry is metal corrosion. Recently, conductive polymers (CPs) have attracted attention due to their economic viability and widespread industrial applications. Upon adsorption, long-chain carbon bonds of polymers provide a blockage for large surface areas of corroding metals. The adsorbed thin films create a barrier between the surrounding environment and the metal substrate. Polypyrrole (PPy), polyaniline (PANI), and polythiophene (PTh) are conducting polymers that are utilized to protect metals and metal alloys against corrosion. A proper selection of synthesis parameters for CPs can improve the anticorrosion behavior of the coatings for metals and metal alloys. This paper has an overview of conducting polymer composite coatings on substrates based on steel, copper, magnesium, aluminum, and their alloys.